SINERGI DI TENGAH PERGUMULAN INSTITUSI BERDASARKAN ANALISIS STRUKTUR SASTRA MAZMUR 20 - Paulus Dimas Prabowo (Phronesis: Jurnal Teologi dan Misi, 2022)
Any institution in the world certainly experiences challenges, including service institutions. When this happens, the synergy between leaders and followers is needed to find a way out. Nevertheless, often synergy does not occur because followers are passive in participating in the crisis that hit. Follower support has a positive impact on leaders. Psalm 20 can provide a biblical basis for synergy between leaders and followers during institutional struggles. The approach used is the hermeneutics of poetry, especially the analysis of its structure and themes. The structure and coherence of the theme can help find the concept of synergism in Psalm 20. The results show that Psalm 20 contains a chiasm structure. With an assessment of the group of persons, repetition of keywords, and types of parallelism, the chiasmus is composed as follows: A (v. 2), B (vv. 3-6), C (v. 7), B' (v. 8 - 9), A' (v. 10). Part C is action while part AA' is inclusion, and both of these parts contain the word 'answer' as a guide to the theme. Part B parallels part B' and supports the theme. The theme of Psalm 20 is waiting for an answer, namely protecting the king's life and victory. The findings show the synergy between leaders and followers. First, evidenced by cooperative behaviour in the action and inclusive sections; second, evidenced by the supportive followers in verses 3-6; and third, by the inspirational leader in verses 7-9.